2014
DOI: 10.1002/chem.201400119
|View full text |Cite
|
Sign up to set email alerts
|

Performance Enhancement of Bulk Heterojunction Solar Cells with Direct Growth of CdS‐Cluster‐Decorated Graphene Nanosheets

Abstract: Two-dimensional graphene-CdS (G-CdS) semiconductor hybrid nanosheets were synthesized in situ by graphene oxide (GO) quantum wells and a metal-xanthate precursor through a one-step growth process. Incorporation of G-CdS nanosheets into a photoactive film consisting of poly[4,8-bis-(2-ethyl-hexyl-thiophene-5-yl)-benzo[1,2-b:4,5-b]dithiophene-2,6-diyl]-alt-[2-(2-ethyl-hexanoyl)-thieno[3,4-b]thiophen-4,6-diyl] (PBDTTT-C-T) and [6,6]-phenyl C70 butyric acid methyl ester (PC70 BM) effectively decreases the exciton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Furthermore, applications of CdS/graphene based composites in other fi elds including solar cells, [ 280,281 ] biosensors, [282][283][284] Generally, with the introduction of graphene, the CdS/ graphene composites exhibit apparently superior photocatalytic activity and photostability than the bare CdS semiconductor due to the strong synergetic interaction between graphene and the semiconductor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, applications of CdS/graphene based composites in other fi elds including solar cells, [ 280,281 ] biosensors, [282][283][284] Generally, with the introduction of graphene, the CdS/ graphene composites exhibit apparently superior photocatalytic activity and photostability than the bare CdS semiconductor due to the strong synergetic interaction between graphene and the semiconductor.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the increasing importance of visible light‐driven semiconductor and carbon materials in materials science, there is no doubt that the number of studies concerning the design and application of CdS/graphene based composite photocatalysts will grow fast in the near future. Furthermore, applications of CdS/graphene based composites in other fields including solar cells, biosensors, photovoltaic devices, adsorption, photoelectrochemistry, etc. have also been reported in the past few years.…”
Section: Discussionmentioning
confidence: 99%
“…Special emphasis has been given on designing reduced graphene oxide (RGO)-semiconductor composites [29][30][31][32][33][34][35][36][37][38][39] to improve the efficiency of the catalyst, because the semiconductor materials can be attached with reduced graphene oxide surface and photogenerated electrons can be extracted easily to graphene. Lee et al reported highly photoactive and low band gap TiO 2 − graphene composite.…”
Section: Introductionmentioning
confidence: 99%
“…An optimal size of phase‐segregated domains is essential whereas very small size of domains may result in nonexistent phase‐pure domains leading to poor device performance. Since it has been established that the size of crystallites is directly influence by the growth rate of the domains in active layer, it is clear that the slow heating of the blend films have provided ideal condition for optimal morphology …”
Section: Resultsmentioning
confidence: 96%